Atos normativos de uma Instituição Federal de Ensino: um instrumento efetivo para os processos institucionais - Cyrilo, Elizabeth Tomazini (2024)
By virtue of the principle of university autonomy, as expressed in the Constitution of the Federative Republic of Brazil of 1988, public universities can self-regulate, allowing them to institutionalize internal regulations aimed at achieving their institutional objectives. This research aims to study the internal regulations of a Federal Educational Institution, with the main objective of investigating the institutional and organizational effects and obstacles of these internal regulations from the perspective of managers from different structures of the institution studied. It seeks to demonstrate the effects of the institutionalization of internal regulations, indicate the need—or lack thereof—for strengthening the institutionalization of internal regulations, and provide support for the strengthening of self-governance and self-regulation of universities. The research employed a quantitative-qualitative approach, with a descriptive case study, focusing on the internal regulations of the Federal University of São Carlos - UFSCar. The main theoretical foundation was Institutional Theory, and a questionnaire was administered to managers from different structures and to members who participated in the commission for the review of normative acts. This allowed for the collection of their perceptions and the analysis of data contributing to the final diagnosis. Empirically, it was demonstrated that the institutionalization of internal regulations contributes to existing elements within the organization such as (i) communication, (ii) execution of functional activities, (iii) decision-making security, (iv) process improvement, and (v) risk control.